Bortezomib and lenalidomide as front-line therapy for multiple myeloma. Issue 9 (September 2014) - Zou, Yandun; Lin, Mingzhen; Sheng, Zhixin; Niu, Shaona
Abstract The objective of the study was to investigate the effects and safety of novel agents such as bortezomib and lenalidomide in the treatment of newly diagnosed patients with multiple myeloma. We performed a comprehensive meta-analysis of randomized controlled trials (RCTs). An initial search yielded 627 citations, of which 10 RCTs enrolling 4534 patients met the inclusion criteria. The addition of bortezomib to first-line therapy significantly prolonged overall survival (OS) (hazard ratio [HR], 0.75 [0.65, 0.87], p < 0.001). On the other hand, the addition of lenalidomide had no impact on survival (HR, 0.88 [0.65, 1.20], p = 0.42). Both lenalidomide and bortezomib consistently improved progression-free survival (PFS) compared with conventional therapy alone. The corresponding HRs were 0.65, 95% confidence interval (CI) [0.55, 0.77] (p < 0.001) for bortezomib and 0.48, 95% CI [0.42, 0.55]; (p < 0.001) for lenalidomide, respectively. Some of the increased adverse events reported were herpes zoster (relative risk [RR], 3.64 [2.23, 5.94], p < 0.001), peripheral neuropathy (RR, 3.59 [1.89, 6.83], p < 0.001) and gastrointestinal effects (RR, 2.19 [1.37, 3.50], p = 0.001) among patients receiving bortezomib, and gastrointestinal effects (RR, 2.36 [1.33, 4.17], p = 0.003) and thromboembolic events (RR, 2.55 [1.48, 4.38], p < 0.001) among patients receiving lenalidomide. Interestingly, treatment with bortezomib seemed to be associated with a lower rate of treatment related mortality (RR, 0.39 [0.18, 0.85], p = 0.02). An increased incidence of second primary cancers was observed in the lenalidomide group (RR 2.61 [1.60, 4.27], p < 0.001). In summary, bortezomib improved OS, and both lenalidomide and bortezomib consistently improved PFS of patients with newly diagnosed myeloma when it was added to standard therapy.